PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERBANKAN PEMERINTAH DAN NON PEMERINTAH PADA TAHUN 2018-2022) - HANDAYANI, R. SRI; ADITYA PRATAMA, YUDHA (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This research aims to analyze the effect of profitability on company value with independent commissioners as a moderating variable in government and non-government banks in 2018-2022. The sample used was 30 financial reports from 30 different banks during the 2018-2022 period. The sampling method used in this research was purposive sampling, so the number of samples was 150. The analytical method used was panel data regression analysis, where data description and descriptive analysis testing were first carried out. The results of this research show that the independent variable, namely profitability, has an effect on company value with a significance level of 0.001. On the other hand, the independent commissioner variable can moderate the influence of profitability on company value